Human parvovirus B19 infection in a pregnant patient resulting in severe hydrops, foetal death and persistent infection. Issue 10 (3rd October 2022) - Bertoldi, Ariel; Colazo Salbetti, María Belén; Rodríguez, Gonzalo; Tenaglia, Magdalena; Hernández, Gabriela; Alfaro, Jimena; Riberi, María Inés; Olivera, Nicolás Lionel; Pedranti, Mauro; Isa, María Beatriz; Adamo, Maria Pilar
Abstract : Human parvovirus B19 (B19V) is the aetiological agent of erythema infectiosum . Primary infection during pregnancy can be transmitted to the foetus and cause foetal abnormalities related to depletion of erythrocyte progenitor cells, including congenital anaemia, hydrops, and foetal death. In this paper we report the detection of B19V infection in a pregnant patient, which onset occurred without appreciable signs and symptoms until she developed inappropriate contractions for gestational age and fluid loss. B19V infection resulted in severe hydrops fetalis with a fatal course for the foetus, while persisted in the mother at least 12 months after foetal death. The objective of this report is to highlight the importance of optimizing B19V diagnosis through early suspicion and testing during pregnancy. Knowing the mother's immune status before or at the beginning of gestation can contribute, together with early diagnosis, to improve the management of patients at risk.